Inovasi Edukasi Berbasis Visual: Teknik Picture Sticker Reward dalam Meningkatkan Motivasi Belajar di MA Darunnajah Kelutan Trenggalek (Al Irfan : Jurnal Ilmu Pendidikan dan Penelitian, 2025)
Learning motivation is one of the key factors in determining students' academic success. However, low learning motivation is still a significant challenge. This study aims to improve the learning motivation of class XII-A students of MA Darunnajah Kelutan Trenggalek through the application of sticker reward pictures as one approach to improve student motivation. This study is included in the category of Classroom Action Research (CAR) which is carried out in two cycles. The subjects of the study were 21 students from the class. Data were collected through observation, interview, and documentation methods, then analyzed descriptively qualitatively. The results of the study showed that the provision of sticker reward pictures had a positive impact on student learning motivation, as indicated by increased active participation, enthusiasm, and consistency in completing tasks. Thus, this strategy can be considered an effective approach in improving student learning motivation, as well as strengthening the use of visual rewards as a supporting tool in learning. The results of the study showed that giving reward picture stickers can increase the learning motivation of class 12A students of MA Darunnajah Kelutan Trenggalek, with the percentage of students who have high motivation increasing from 14.3% in cycle I to 71.4% in cycle II. Thus, it can be concluded that giving picture stickers is effective in increasing the learning motivation of students in the class.